PENGARUH KOMPETENSI , MOTIVASI INTRINSIK TERHADAP KINERJA GURU MADRASAH ALIYAH SE- KECAMATAN MARGOYOSO - PATI - Abdul Kafi, 12.52.02.0002 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to identify and examine the effect of competence and intrinsic motivation on the teachers performance in the school culture moderated by PrivateIslamic High School( MA ) in district Margoyoso Pati., the sample used in this study was 120 people . The specific purpose of this study is to examine and analyze the influence of competence and intrinsic motivation on teachers performance moderated by school culture. The use of this study is to explain and the extend previous study. This study used the data testing method using primary data obtained by questionnaire . The research method used a computerized approach to the statistical program SPSS ( Statistics Package for Social Science ) included test validity with factor analysis , reliability tests with alpha cronbach formula , linear regression analysis by using the moderating effects test. The result showed that : Competency had the positive and significant impact on the teachers performance. It was 0,619. The intrinsic motivation had no significant influence on the teachers performance. the school culture hadpositive and significant impact on the teachers performance. It was 0,210. The school culture moderation had not significant on the influence of competence on teachers performance . The school culturemoderationhad not significant on the influence of intrinsic motivation on teachers performance. Keywords : Competence , intrinsic motivation, school culture , performance and moderation